(untitled) (المجلة الدولية للعلوم التربوية والآداب, 2025)
This study investigates the challenges faced by Libyan EFL students in spontaneous listening and speaking. Despite proficiency in grammar and reading, students struggle with real-time communication due to various linguistic, cognitive, and psychological barriers. Using a mixed-methods approach, the research integrates quantitative data from a Likert-scale survey and qualitative insights from student interviews. Findings reveal significant anxiety, limited practice opportunities, and reliance on Arabic as a cognitive strategy. The study highlights the need for curriculum reforms that emphasize communicative competence and suggests actionable strategies to enhance oral proficiency among Libyan learners.